Meningkatkan Keterlibatan dan Pemahaman Siswa Pada Mata Pelajaran Ilmu Pengetahuan Alam Melalui Metode Kombinasi Flipped Classroom - Selasih, Rara Sekar; Pertiwi, Santhi; Ramdani, Akhmad Subkhi (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2024)
This study focuses on improving student engagement and understanding in Natural Science (IPA) for third graders at SD Negeri Jatiwarna 4, Pondok Melati, Bekasi City. Utilizing classroom action research over two cycles with 32 students, the findings reveal that the flipped classroom method, combined with group assignments and peer teacher involvement, significantly enhances student interest and engagement. There is a marked increase in learning completion rates from the first to the second cycle, demonstrating the effectiveness of these innovative teaching strategies. The results highlight the need for creative teaching approaches to enhance learning outcomes in elementary science education. The practical implications of this study suggest that educators should adopt flipped classroom models to promote active learning, allowing students to engage with content at their own pace before class discussions. Additionally, schools can benefit from encouraging peer teaching initiatives, where students learn from each other, fostering collaboration and enhancing their understanding of complex concepts. Group assignments can further enhance teamwork skills and increase student motivation, as students feel more accountable to their peers.